ALLELOPATH IC EFFECT OF SEED OF SWEET CLOVER (MEL/LOTUS IND/CA L.) AND NaCl ON GERMINATION AND SEEDLING GROWTH OF RicE (Biological Sciences - PJSIR, 2002)
The effect of seed of sweet clover (!vfelilotus indica L.)  was  eval uated  alone  or  in  combination  wi th  NaCl  on  the germination and seedling growth  of  rice.  As  compared  to  control,  there  was  significant  inhibi tory  effect  on  germi nation and  the  maximum  reduction  o[  25%  was  recorded  when  0.4%  NaCl  and  weed   seed  were  applied  together.  The  growth of both shoot and root significantly decreased under NaC l as wel l as with the placement of weed seed. Root growth was affected more than shoot. The effect of NaCl was accentuated in  the presence  of weed  seed. Reduction  in  shoot length was 40 and 45% wi th weed seed alone and al 0.2% NaCl, respectively. The correspondi n g figures for root were 95% and 94° o, respectively. Tt wa s concl uded lhal weed seed or sweet clover i n co111 bi11alio11 with NaCl had signiftc,1nl inhi bi to,y effects  on  germi nation  and  seedling  growth  of rice.